Pathogenesis studies of African swine fever virus isolates from Bali and East Nusa Tenggara as a basis for inactivated vaccine development - I Wayan Masa Tenaya; Kadek Karang Agustina; Ketut Suada; Made Sukada; Romy Muhammad Dary Mufa; Ida Ayu Pasti Apsari; I Made Dwinata; Ida Bagus Komang Ardana; Made Damriyasa; Tri Komala Sari; Nyoman Mantik Astawa; Ketut Eli Supartika; Ketut Wirata; Nyoman Suarsana; Nyoman Suartha (Jurnal Medik Veteriner, 2026)
African swine fever (ASF) is a highly contagious and lethal disease of pigs for which no effective vaccine is currently available. This study evaluated the pathogenicity of field African swine fever virus (ASFV) isolates from Bali and East Nusa Tenggara and assessed their potential for inactivated vaccine development using spleen-derived antigens. Based on the qPCR results, among all ASFV isolates tested, only the Bali isolate, designated B1, exhibited the highest DNA concentration, suggesting that this sample contained the highest ASFV titer. Consequently, the B1 isolate was selected and processed into chemically treated (CT-ASFV) and non-treated (NCT-ASFV) formulations. In the pathogenesis trials, pigs inoculated with NCT-ASFV developed acute ASF and died within 12 days, whereas those receiving CT-ASFV exhibited no clinical signs of ASF and showed no evidence of viral replication. In the vaccination trial, pigs immunized with CT-ASFV emulsified in Montanide™ ISA 50 V2 demonstrated survival in two out of three animals (67%) following challenge with a virulent strain, while all control animals succumbed to infection. Despite the absence of detectable humoral responses as determined by ELISA, the observed protection suggests a potential role for cell-mediated immunity. These findings indicate that the B1 isolate was highly virulent and represents a promising candidate for the development of an inactivated ASF vaccine. Further evaluation in larger-scale field trials is warranted.